Taxation : local government and real property taxation vol. 5 - Domondon, Abelardo T. (Manila, Philippines : GIC Enterprises & Co. Inc., 2013)
This Volume V was updated bearing in mind the Note to coverage of the Law on Taxation for the 2013 bar Examinations.
I. Part I. Local Government Taxation -- II. Part II. Real Property Taxation.
Keywords: TAXATION -- LAW AND LEGISLATION -- PHILIPPINES